Pola Komunikasi Dosen dan Mahasiswa dalam Meningkatkan Efektivitas Pembelajaran Pendidikan Agama Islam - Ibnu Fiqhan Muslim; Mansur; Nur Sodik; Fahmi Salsabila (CV. Biha Cendekia, 2026)
This study aims to analyze communication patterns between lecturers and students in Islamic Religious Education (PAI) learning and identify factors that influence communication effectiveness in supporting learning success. The study was conducted at Indraprasta PGRI University Jakarta with subjects including lecturers teaching Islamic Religious Education (PAI) and students from various study programs taking the course. The method used was a descriptive qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. Data analysis refers to the Miles, Huberman, and Saldaña model through the stages of data condensation, data presentation, and conclusion drawing, while data validity was tested using source and technique triangulation. The results showed that the dominant communication pattern was two-way communication, where 80% of respondents stated that lecturers consistently provided opportunities for discussion, and 90% of observations showed a question and answer session during lectures. In addition, 90% of students considered lecturers' language communicative, 85% felt more confident in expressing their opinions due to open communication, and 95% stated that the use of digital media such as WhatsApp, Google Classroom, and Zoom facilitated academic interaction. However, obstacles such as low levels of questioning skills, time constraints, and internet connection issues were still encountered. It was concluded that interactive, humanistic, and open communication supported by digital media and Islamic values significantly contributed to increased participation, motivation, understanding of the material, and the quality of Islamic Religious Education learning at Indraprasta PGRI University Jakarta.